The coastal resources of Brunei Darussalam status, utilization and management. - Silvestre, G.; Matdanan, H.J.H.; Sharifuddin, P.H.Y.; Silva, M.W.R.N. de; Chua, T.E. (eds.) (Dept. of Fisheries, Ministry of Industry and Primary Resources, 1992)
ICLARM Conf. Proc. (34)